Orden en los ejercicios de fuerza sobre el rendimiento de los judocas - Saraiva, A. R.; Borba-Pinheiro, C. J.; Reis, V. M.; Bitencourt da Silva, J. L.; Drigo, A. J.; Mataruna-Dos-Santos, L. J.; Novaes, J. S. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
OBJECTIVE: To analyze the effect of strength exercises using different orders for upper and lower limbs on the specific performance of junior judo athletes. METHODS: 39 male athletes were divided into three groups: experimental-EG1, experimental-EG2 and control group. Experimental groups performed with intensities 80-90% of strength and power for 12 weeks. The exercise-order for EG1 followed an upper to lower limb sequence and EG2 performed the same exercises in reverse. The Special Judo Fitness Test (SJFT) was used in the assessment.RESULTS: Experimental intra and inter-groups showed differences (p<0.05) in the throws-falls and SJFT-index, but the EG2 showed best results. CONCLUSIONS: The SJFT-variables had better results to exercises order in EG2.